A Framework for the Design of Multi-Channel Services - Sousa, Rui (2013)
The objective of this paper is to identify the key strategic design decisions which make up a design specification for Multi-Channel Service Delivery Systems (MC SDSs). Our work extends Roth and Menor’s (2003) seminal service design framework, based on a theory-building case study conducted in the context of MC retail banking services. We describe and classify a set of SDS design choices which are specific to MC services, and which provide a framework to assist future research addressing the classification and performance assessment of alternative MC SDS designs.